Feedlot performance, feeding behavior, carcass and rumen morphometrics characteristics of Nellore cattle submitted to strategic diets prior the adaptation period - Pereira, M. C.S. [UNESP]; Dellaqua, J. V.T. [UNESP]; Sousa, O. A. [UNESP]; Santi, P. F. [UNESP]; Felizari, L. D. [UNESP]; Reis, B. Q. [UNESP]; Pinto, A. C.J. [UNESP]; Bertoldi, G. P. [UNESP]; Silvestre, A. M. [UNESP]; Watanabe, D. H.M. [UNESP]; Estevam, D. D. [UNESP]; Arrigoni, M. D.B. [UNESP]; et al. (Elsevier, 2020)
The study was designed to evaluate the effects of either nutritional restriction or intake of concentrate feedstuffs before beginning the adaptation period on days to adapt, feedlot performance, feeding behavior, carcass characteristics, rumen and cecum morphometric of Nellore cattle. The experiment was designed as a completely randomized block, replicated 8 times (4 animals/pen), in which 96 Nellore bulls with an initial body weight (BW) of 365.52 ± 39.19 kg were fed in 24 pens according to the treatments, as follows: Restriction (Tifton hay fed at 1.4% of BW + mineral supplement); Control (Tifton hay fed ad libitum + mineral supplement) and Concentrate (Tifton hay fed ad libitum + 0.5% of BW of a mix of concentrate feedstuffs and mineral supplement). This study lasted 144-d, divided into 2 periods, as follows: 32-d of preadaptation, in which cattle were submitted to the treatments previously described, and 112-d of finishing period, where all cattle were fed the same diets. At the end of preadaptation period, one animal per pen was slaughtered (n = 24) for carcass, cecum and rumen evaluations, and the remaining 72 animals were harvested after 112-d of finishing period. No significant (P > 0.10) treatment effect was observed for days to adapt to the high-concentrate diet, which was 14 days (SEM: 0.63). Cattle submitted to restriction had greater (P < 0.10) ADG in kg (Restriction: 1.29; Control: 1.06; Concentrate: 1.18; SEM: 0.04), DMI in kg (Restriction: 9.19; Control: 8.56; Concentrate: 8.86; SEM: 0.28), G:F ratio (Restriction: 0.140; Control: 0.124; Concentrate: 0.133; SEM: 0.004), number of papillae (Restriction: 72.76; Control: 63.28; Concentrate: 62.99; SEM: 3.41) and absorptive surface area in cm2 of rumen wall (Restriction: 26.89; Control: 22.29; Concentrate: 22.30; SEM: 1.36) compared with cattle in the control group at the end of the study. Cattle submitted to either restriction or concentrate supplementation had greater (P < 0.10) final HCW in kg (Restriction: 285.35; Control: 274.10; Concentrate: 287.30; SEM: 4.51), final 12th rib fat in mm (Restriction: 4.57; Control: 3.93; Concentrate: 4.50; SEM: 0.21) and final Biceps femoris fat thickness in mm (Restriction: 6.14; Control: 5.23; Concentrate: 5.91; SEM: 0.23) compared with cattle in the control group at the end of the study. Thus, either restriction or concentrate supplementation before beginning the adaptation period to high-concentrate diets did not impact adaptation length, and both may be used as nutritional strategies to improve performance and carcass characteristics of feedlot Nellore cattle.
Keywords: Compensatory growth; Papillae; Period; Rumen; Zebu